Teknologi Pembelajaran Dalam Pengembangan Profesional Pendidikan Agama Islam di Indonesia: Analisis Bibliometrik - Ismail, Ismail (Lembaga Penelitian dan Pendidikan Mandala, 2022)
Technological developments have penetrated in many aspects of life and currently have developed to accompany important aspects in the development of Islamic religious education in a sustainable manner. Islamic teachings regard the pursuit of individual growth through education as a sacred and lifelong task. As a form of continuous development, efforts to increase knowledge, wisdom, and skills are considered as an obligation of a Muslim. Finally, the development of technology and the progress of thinking in an Islamic perspective must be in line. This study aims to conduct a bibliometric analysis of learning technology in the professional development of Islamic religious education in Indonesia. In the current bibliometric analysis study, we used SCOPUS as a database or information which was further analyzed according to the flow and several screening processes according to the objectives of this study. The bibliometric analysis was carried out on April 26, 2022 by exploring the SCOPUS database, and in the 'search documents' entering keywords or keywords for the study title in the English version so that SCOPUS could read and crawl it adequately. Keyword inserted TITLE-ABS-KEY (learning AND technology AND in AND on AND Islamic AND education). This is an initial screening process, which is not limited to year, subject area, document type and source, and other types of restrictions. At this stage, as many as 170 documents were found in the range from 1994 to 2022 (no data or documents were found before 1994 with keywords inserted). The second screening was scanned with the same keywords as the first screening and added with the keyword 'Indonesia' in the 'search documents' menu. conference paper' on all subject areas. The results found as many as 24 documents in the span of that year. Finally, the results of this study can be a reference and preference for the study of the development of Islamic religious learning, especially for scholars engaged in Islamic education technology in all fields of science.